Case report: Treatment of left-sided valve endocarditis using the Transapical AngioVac System and cerebral embolism protection device: A case series - Fiocco, Alessandro; Colli, Andrea; Besola, Laura (Frontiers in Cardiovascular Medicine, 2023)
The AngioVac System (AngioDynamics, Latham, NY) was developed for treatment of right sided heart and intravenous masses. Lately it was employed to deal with left sided heart masses, in particular native valve endocarditis (NVE) and valve prostheses endocarditis (VPE) in high-risk patients. Left-sided heart endocarditis, is burdened by high morbidity and mortality also when open heart surgery is performed. Recently, patients presenting with left NVE and VPE have been treated with off-label use of AngioVac System, even if the solution presents a considerable cerebral embolization risk issue, due to risk of fragmentation rather than complete en-bloc aspiration of the masses. Percutaneous cerebral embolism protection system is currently used in TAVI procedures, especially when the native valve present extensive calcifications and consequent significant embolic risk. We here present a clinical case series of combined utilization of AngioVac System and cerebral embolism protection system Triguard (Keystone Heart Ltd., Herzliya, Israel) to treat left NVE, and VPE in prohibitive-surgical-risk patients.